Modeling wide range of viscoelastic-viscoplastic behavior of Araldite LY 564 epoxy using cooperative viscoplasticity theory based on overstress model - Bakbak, Okan; Colak, Ozgen (WILEY, 2023)
The rate-dependent properties of epoxy (Araldite LY 564) were successfully addressed by dynamic mechanical analysis (DMA), quasi-static compression tests (strain rates: 1.E-3, 1.E-2, and 1.E-1 /s), Split Hopkinson Pressure Bar (SHPB) testing (strain rates: 875 and 770/s) and stress relaxation experiments (strain levels: 3.16 and 7.15%) are simulated by a micromechanically based constitutive model. The used model is Cooperative-Viscoplasticity Theory Based on Overstress (VBO) model. The majority of works about modeling polymers are limited to modeling quasi-static tension-compression behaviors and predicting elasticity modulus and yield strength. In this work, the effectiveness of the Cooperative-VBO model is verified and validated by simulating a wide range of material behaviors of Araldite LY 564. Material parameters of the model are determined by using storage modulus obtained from DMA and quasi-static compression test at a strain rate of 1.E-1 /s. High strain rate behaviors and stress relaxation behaviors are predicted. The behaviors from quasi-static to high strain rate, from stress relaxation at different strain levels to storage modulus, respectively, are predicted with a single set of material parameters. Simulation and prediction results revealed the effectiveness of the proposed model.
Keywords: cooperative VBO; epoxy; high strain rate; modeling; relaxation; HIGH-DENSITY POLYETHYLENE; STRAIN-RATE; DEFORMATION-BEHAVIOR; AMORPHOUS POLYMERS; STRESS-RELAXATION; MECHANICAL-PROPERTIES; TEMPERATURE; RESIN; VBO; Polymer Science